Modeling, Control, and Simulation of a Common-Emitter Switched Amplifier with a Voltage-Variable Gain - Campos-Salazar, José M.; Nicolás-Apruzzese, Joan; García-Rojas, Gabriel (Journal of Electronics and Electrical Engineering, 2025)
A novel topology of a switched amplifier configured as a common-emitter voltage variable gain amplifier, along with the implementation of a control system aimed at regulating the output voltage is introduced in this article. A key focus of this work is addressing the challenge of output voltage regulation in the presence of variations in voltage gain caused by changes in the output load. The proposed topology integrates a standard common-emitter amplifier with an additional switch connected to the emitter terminal, which enables implementing an efficient control over the amplifier's voltage gain. The feasibility and operation of the presented system are satisfactorily evaluated through simulation studies.